ANALISIS HUBUNGAN DUKUNGAN SUAMI DENGAN KONDISI FISIK DAN PSIKIS IBU PADA SAAT PERSALINAN DI RSU MUHAMMAD ALI KASIM KABUPATEN GAYO LUES PROVINSI ACEH TAHUN 2024 - Nia Syafriati; Gerry Silaban; Peny ariani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2026)
Husband's support is often known by another term, namely support in the form of sympathy, which is proof of affection, attention, and a desire to listen to other people's complaints. Needs, abilities, and sources of support change throughout a person's life. The Family is the first environment known to individuals in their socialization process. The aim of the research to analyze the relationship between the husband's support and the mother's physical and psychological condition during childbirth at Muhammad Ali Kasim Hospital, Gayo, Aceh Province., the population of 40 respondents at Muhammad Ali Kasim Hospital , Gayo Lues Aceh, the purposive of the sampling technique, the data was obtained from the results of interviews by distributing questionnaires that had been prepared by the researcher. The Data of analysis was carried out univariately and bivariately using the chi-square test with an alpha value (a) of 0.05. The results of research using the chi-square test obtained a p-value of 0.000 (p < 0.05). It can be concluded that Ho was accepted, which means there is a relationship husband's support with the mother's physical condition during childbirth at Muhammad Ali Kasim Hospital, Aceh. The results of the research using the chi-square test, the p-value was obtained at 0.002 (p<0.05) it can be concluded that Ho was accepted, which means There is a relationship between the husband's support and the mother's psychological condition during childbirth at Muhammad Ali Kasim Hospital, Gayo Lues Aceh.